2012
DOI: 10.1074/jbc.m112.378513
|View full text |Cite
|
Sign up to set email alerts
|

A Leucine Zipper Motif Essential for Gating of Hyperpolarization-activated Channels

Abstract: Background: It is poorly understood how hyperpolarization-activated cyclic nucleotide-gated channels (HCNs) function. Results: We have identified a leucine zipper in the S5 segment of HCNs, regulating hyperpolarization-activated and instantaneous current components. Conclusion:The leucine zipper is essential for HCN channel gating. Significance: The identification and functional characterization of the leucine zipper is an important step toward the understanding of HCN channel function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Our simulations reveal that pore opening involves a tradeoff between a strengthening of the S5/S6 interface at the expense of a weakening of the S6-S6 interface. This is consistent with previous mutagenesis of a leucine zipper motif between S5 and S6, which demonstrated that disruption of this motif reduces the ability of the VSD to drive pore opening ( Wemhöner et al, 2012 ). While stabilization of the S5/S6 interface upon opening is seemingly at odds with the model of Flynn and Zagotta, this difference can be reconciled by examining the mechanism of S6 gating.…”
Section: Discussionsupporting
confidence: 92%
“…Our simulations reveal that pore opening involves a tradeoff between a strengthening of the S5/S6 interface at the expense of a weakening of the S6-S6 interface. This is consistent with previous mutagenesis of a leucine zipper motif between S5 and S6, which demonstrated that disruption of this motif reduces the ability of the VSD to drive pore opening ( Wemhöner et al, 2012 ). While stabilization of the S5/S6 interface upon opening is seemingly at odds with the model of Flynn and Zagotta, this difference can be reconciled by examining the mechanism of S6 gating.…”
Section: Discussionsupporting
confidence: 92%
“…The most recent work shows that among the structural particularity of HCN channels, a leucine-zipper motif between the S5 and S6 segments seems to be involved by stabilizing the closed state at depolarized potentials. 21 As stated above, the I f current is voltage dependent (activated by hyperpolarization; see Figure 2). An unusual property of HCN channels involves the permeability to both Na + and K + (higher permeability to K + ions than to Na + ions).…”
Section: The Hcn Channel Familymentioning
confidence: 99%
“…The open probability of the channel was not altered by L29A substitution and was similar to the wild-type. Leucine is known to interact with the hydrophobic lipid bilayer 58 and substituting it with alanine potentially alters this interaction. This disruption in lipid interaction could have possibly altered the stability of the pore region as also seen in hyperpolarization-activated cyclic nucleotide-gated channels 58 .…”
Section: Discussionmentioning
confidence: 99%